Foreign direct investment decision-making motives for multinational Enterprises: A study of eight firms in an emerging economy - Kuzey, Cemil; Dinc, Muhammet Sait; Khan, Farzan Ullah; Raj, Victor (Journal of Management, Economics, and Industrial Organization, 2021)
Foreign direct investment (FDI) is a key element of the global economy, which is an engine of employment, technological progress, productivity improvements, and, ultimately, economic growth, especially within emerging countries. As an emerging country, India has attracted the attention of multinational enterprises in recent years. This study aims to explore a variety of foreign direct investment decision-making motives of multinational enterprises which have entered the market in India. Qualitative research methodology was incorporated in this study to investigate different FDI decision-making motives by means of interviews with the representatives of eight companies who hold enterprises in India in which the study findings regarding the various entry modes, location choices, strategies, opportunities and challenges faced by multinational entities in the Indian market were explored.